A torque-based method demonstrates increased rigidity in Parkinson's disease during low-frequency stimulation - Little, S; Joundi, R; Tan, H; Pogosyan, A; Forrow, B; Joint, C; Green, A; Aziz, T; Brown, P (2012)
Low-frequency oscillations in the basal ganglia are prominent in patients with Parkinson's disease off medication. Correlative and more recent interventional studies potentially implicate these rhythms in the pathophysiology of Parkinson's disease. However, effect sizes have generally been small and limited to bradykinesia. In this study, we investigate whether these effects extend to rigidity and are maintained in the on-medication state. We studied 24 sides in 12 patients on levodopa during bilateral stimulation of the STN at 5, 10, 20, 50, 130 Hz and in the off-stimulation state. Passive rigidity at the wrist was assessed clinically and with a torque-based mechanical device. Low-frequency stimulation at <20 Hz increased rigidity by 24 % overall (p - 0.035), whereas high-frequency stimulation (130 Hz) reduced rigidity by 18 % (p - 0.033). The effects of low-frequency stimulation (5, 10 and 20 Hz) were well correlated with each other for both flexion and extension (r - 0.725 ± SEM 0.016 and 0.568 ± 0.009, respectively). Clinical assessments were unable to show an effect of low-frequency stimulation but did show a significant effect at 130 Hz (p - 0.002). This study provides evidence consistent with a mechanistic link between oscillatory activity at low frequency and Parkinsonian rigidity and, in addition, validates a new method for rigidity quantification at the wrist. © The Author(s) 2012. This article is published with open access at Springerlink.com.